Road Management Policy : An Approach to the Evaluation of Road Agency Performance - Pinard, Michael Ian (World Bank, Washington, DC, 2015)
Road transport is the most pervasive of all transport modes in Africa and is central to the socioeconomic growth and development of all countries in the region. For it to be effective as a catalyst for development, road provision must be institutionally, economically, financially, socially, and environmentally sustainable. The main objective of the present document is to analyze the commercialized road management (CRM) and publicly available specification (PAS) evaluation approaches for assessing road agency performance in road asset management. The document also considers how the two approaches can be amalgamated to enhance the evaluation of roads agency performance in terms of key benchmarks for good road asset management practice. Finally, the document reflects on indicators that can be incorporated in an appropriate asset management evaluation framework to: (1) measure the progress being made towards commercialization of road administrations; and (2) monitor the performance of roads agencies in terms of the efficiency and effectiveness with which they undertake their responsibilities in the road sub-sector. The report is structured as follows: section one presents the background to the working paper, including its purpose and structure. Section two considers the need for a holistic approach to assessing road agency performance in road asset management. Section three provides an overview of the alternative approaches to assessing roads agency capacity in asset management and their ability to pinpoint those key elements that contribute to effective and efficient road asset management. Section four compares and contrasts the outcomes of the assessment of road agency capacity in road asset management produced by the alternative approaches and uses data from three countries to compare the outcomes produced by the two methods. Section five considers various performance measures and indicators that can be adopted to monitor and report upon on a continuing basis road agency performance in asset management. Section six presents the findings, conclusions, and recommendations of the study including a plan of action to implement the best aspects of both approaches to assessing roads agency capacity in road asset management.